answersLogoWhite

0


Best Answer

42

User Avatar

Wiki User

โˆ™ 2012-08-17 18:46:37
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.75
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1048 Reviews

Add your answer:

Earn +20 pts
Q: What is 1 minus the qoutient of r and 7?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

How do you write 1 minus the quotient of r and 7 in algebraic expression?

It is 1 - r/7


What is 1 minus the quotient of r and 7?

1 - r/7 Another way to write the same thing is 7/7-r/7 which is (7-r)/7


Why does minus of minus equals plus?

The negative of a negative number is a positive number. The reason for this is that the first negative is a place holder for -1. When you have - - 4, that translates into -1 x -4. When you multiply two negative numbers, you get a positive.For example:- - 7 = -1 x -7 = 7- - r = -1 x -r = r


What is the answer to this math problem 3r squared minus 12r minus 15?

That factors to 3(r - 5)(r + 1) r = 5, -1


What is r in this equation and how do you do it minus 5 equals 7 plus 3r?

-5 = 7 + 3r | subtract 7 -12 = 3r | divide by 3 -4 = r


What are the factors of 7 and 11?

7's r 7& 1. 11's factorz r 11 & 1


Prove that nCr plus nCr minus 1 equals n plus 1Cr?

nCr + nCr-1 = n!/[r!(n-r)!] + n!/[(r-1)!(n-r+1)!] = n!/[(r-1)!(n-r)!]*{1/r + 1/n-r+1} = n!/[(r-1)!(n-r)!]*{[(n-r+1) + r]/[r*(n-r+1)]} = n!/[(r-1)!(n-r)!]*{(n+1)/r*(n-r+1)]} = (n+1)!/[r!(n+1-r)!] = n+1Cr


What is fifty divided by seven remainder?

50 / 7 = 7 r 1 or 7 1/7


How do you solve for r when G equals A divided by 1 minus r?

You would take the following steps for G = A / (1-R):G = A / (1-R)Multiply by (1-R):G * (1-R) = ADivide by G:(1-R) = A/G1-R = A/GSubtract 1:-R = (A/G) - 1Divide By -1:R = -((A/G) - 1)Check Work:Original Problem:A = 12; R = 5G = 12 / (1-5)G = -3Solving For R:R = -((12/-3)-1)R = 5Therefore, R= -((A/G)-1)


What is 12 minus r?

The value of 12 - r will depend on r.


What does the hexa number E78 in radix 7 with explanation?

E7816 = 14 x 256 + 7 x 16 + 8 = 370410 3704 ÷ 7 = 529 r 1 529 ÷ 7 = 75 r 4 75 ÷ 7 = 10 r 5 10 ÷ 7 = 1 r 3 1 ÷ 7 = 0 r 1 ⇒ 370410 = 135417 ⇒ E7816 = 135417 Alternatively, doing the arithmetic in hexadecimal: E7816 ÷ 716 = 21116 r 1 22116 ÷ 716 = 4B16 r 4 4B16 ÷ 716 = A16 r 5 A16 ÷ 716 = 116 r 3 116 ÷ 716 = 016 r 1 ⇒ E7816 = 135417


What is r2 plus 6r-7 quadratically factorized?

r2+6r-7 = (r+7)(r-1) when factored

People also asked